Upaya Peningkatan Kompetensi Guru Dalam Menyusun Rencana Pelaksanaan Pembelajaran Melalui Pembinaan Terstruktur - Lilik Suhartini (FKIP UNIVERSITAS PAKUAN, 2015)
This research is action research in school which aims to determine whether through a structured development efforts can improve the teachers competences in preparing lesson plan at SMP Negeri 3 Ciawi, Bogor, Indonesia. Research instrumen used the observation sheet. Action research was conducted in two cycles. In the first cycle, through the firts structured development show that the teachers’s competence in preparing lesson plan is 72% in good category. Its before the treatment was 66.89%. In the second cycle obtained changes in teacher competence in preparing lesson plan is 87.9%. Its in a very good category. Based on data can be concluded that through the structured development efforts can improve the teacher competence in preparing lesson plan.